The suprahiazmatic nucleus of the forward hypothalamus destruction and circadian rhythms of moving activity, body temperature and renal excretion of Nа+, Cа2+, K+, Li+ in rats in summer solstice - T. A. Zamoshchina; M. V. Meleshko; S. V. Logvinov; A. V. Matveуenko; L. N. Novitskaya; Ye. V. Ivanova (Бюллетень сибирской медицины)
In summer solstice it was established that right or left suprachiazmatic nucleus lesion breaks circadian rhythms of rat's moving activity in «open field» and lithium urine excretion. Damage of the left nuclei in a greater degree affects formation circadian rhythm of sodium renal excretion, destruction of the right nuclei - the calcium rhythm organization. The rhythms of body temperature and potassium urine excretion find weak sensitivity to reenergizing right or left suprachiazmatic nucleus. At destruction right or left suprachiazmatic nucleus are formed rhythm's desynchronization, character and expressiveness are defined by an illumination mode.